Distance exercised during submaximal training on race winnings for Thoroughbred racehorses - Berkman, Carolina [UNESP]; Teixeira, Luisa Gouvea [UNESP]; Pereira, Marsel Carvalho; Sampaio, Rita De Cássia de Lima [UNESP]; Bernardi, Nara Saraiva [UNESP]; Lacerda Neto, José Correia de [UNESP]; Queiroz Neto, Antonio de [UNESP]; Ferraz, Guilherme de Camargo [UNESP] (Universidade Federal de Santa Maria, 2015)
Evaluations of the physical fitness of Thoroughbred racehorses have been correlated with race earnings, but few reports exist about the influence of the distance exercised during training on both physical conditioning indices and financial productivity. During one training season sixteen claiming Thoroughbred horses were subjected to submaximal training and monitored by a global positioning system (GPS) coupled to a heart rate monitor. After initial and single monitoring, the horses were distributed into two groups of eight individuals each; one group exercised short distances (SD) between 1600 and 1900m, while the other exercised long distances (LD) between 2000 and 2350m. The duration (min) and mean and maximal velocities (ms-1)attained during each session were determined, as well as the difference in distances exercised (m) between official races and each training session. Blood lactate concentration ([LA]) during recovery was also determined. Student's t-test was used for a non-paired analysis, with P≤0.05 considered significant. The winnings (USD) of each horse were correlated with the peak heart rate (HRpeak) attained during the training session. The distances exercised in the training sessions were greater in relation to the official races distances by 24.7% and 40% for SD and LD, respectively. Lactatemia did not differ between the groups. The HRpeak obtained during the training session was lower in LD group. The velocity at which the heart rate reached 200 bpm (V200) was higher in LD group. There was a moderate correlation (r= 0.42) between the highest winnings and lowest HRpeak. The horses that ran longer distances during their submaximal training session had better cardiac conditioning and tendency to increase financial productivity

Avaliações da aptidão física de cavalos Puro Sangue Inglês (PSI) têm sido correlacionadas com o ganho financeiro, mas a influência da distância percorrida durante o treinamento, tanto sobre índices de condicionamento físico como na produtividade financeira tem sido pouco relatada. Monitoraram-se, por meio de global positioning system (GPS) acoplado a frequencímetro, numa temporada de treinamento, dezesseis equinos da raça PSI, de uma mesma categoria, submetidos a treinamento submáximo. Após o monitoramento inicial e único de uma sessão de treino, os equinos foram distribuídos em dois grupos de oito componentes (DC e DL) diferenciados de acordo com a distância percorrida durante cada sessão de treino, sendo DC para distância curta e DL para distância longa. Dessa maneira, DC e DL percorreram distâncias entre 1600-1900 e 2000-2350 metros, respectivamente. Determinaram-se o tempo e as velocidades médias e máximas atingidas (m s-1), bem como a diferença entre as distâncias percorridas (m) entre as corridas oficiais e as sessões. A produção de lactato sanguíneo durante a recuperação foi quantificada. Empregou-se teste t de student para análise não pareada, sendo P≤0,05. Correlacionaram-se os ganhos financeiros (USD) de cada cavalo com afrequência cardíaca de pico (FCpico) atingidas durante as sessões. As distâncias percorridas nos treinos foram maiores em relação às corridas oficiais em 24,7% e 40% para DC e DL, respectivamente. A lactatemia não diferiu entre os grupos. A frequência cardíaca de pico (FCpico) obtida durante as sessões foi menor para o grupo DL. A velocidade que a frequência cardíaca atingiu 200 bpm (V200) foi maior para DL. Houve correlação moderada entre os maiores ganhos financeiros e menores FCpico. Os cavalos que treinaram maiores distâncias durante sessões de treinamento submáximo tiveram melhor condicionamento cardíaco e maior produtividade financeira
Distância percorrida durante treinamento submáximo sobre rendimentos de cavalos de corrida da raça Puro Sangue Inglês
Keywords: Horse; Distance exercised; Heart rate; Lactate; Race performance; Race earnings; Cavalo; Distância percorrida; Frequência cardíaca; Lactato; Desempenho; Rendimentos de corrida